2023
DOI: 10.1186/s12912-023-01228-6
|View full text |Cite
|
Sign up to set email alerts
|

Sexual harassment as experienced by nurses from selected healthcare facilities in Ghana

Abstract: Background Workplace Sexual Harassment (WSH) remains a major occupational health hazard to many nurses globally. Despite the negative impact of WSH on health and safety of nurses, there are limited studies exploring sexual harassment experiences of nurses in the line of duty in Low- and middle-income countries (LMICs) including Ghana. Aim This study aimed at exploring the lived sexual harassment experiences among nurses working in healthcare facili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…In Ghana, there are very limited studies on work-related sexual harassment involving nurses,13 a situation that impedes the appreciation of the problem and limits the implementation of evidence-based interventions to address it. Meanwhile, studies on sexual harassment in some sectors in Ghana revealed high prevalence in institutions such as education,22 sports,23 faith-based organisations24 and healthcare 25. For instance, Boafo et al 13 reported that about 12.2% of the nurses surveyed in Ghana experienced work-related sexual harassment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Ghana, there are very limited studies on work-related sexual harassment involving nurses,13 a situation that impedes the appreciation of the problem and limits the implementation of evidence-based interventions to address it. Meanwhile, studies on sexual harassment in some sectors in Ghana revealed high prevalence in institutions such as education,22 sports,23 faith-based organisations24 and healthcare 25. For instance, Boafo et al 13 reported that about 12.2% of the nurses surveyed in Ghana experienced work-related sexual harassment.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, studies on sexual harassment in some sectors in Ghana revealed high prevalence in institutions such as education, 22 sports, 23 faith-based organisations 24 and healthcare. 25 For instance, Boafo et al 13 reported that about 12.2% of the nurses surveyed in Ghana experienced work-related sexual harassment. However, Boafo et al ’s 13 study was limited to only nurses working in hospitals and did not include other nurses working at lower-level healthcare facilities such as polyclinics and health centres.…”
Section: Introductionmentioning
confidence: 99%